2015
DOI: 10.1139/cjm-2015-0118
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the VP39 envelope protein from Singapore grouper iridovirus

Abstract: Singapore grouper iridovirus (SGIV) is a major pathogen that causes heavy economic losses to the grouper aquaculture industry in China and Southeast Asian countries. In the present study, a viral envelope protein, VP39, encoded by SGIV ORF39L, was identified and characterized. SGIV ORF39L was found in all sequenced iridoviruses and is now considered to be a core gene of the family Iridoviridae. ORF39L was classified as a late gene during in vitro infection using reverse transcription-polymerase chain reaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…However, little research has been performed concerning the molecular mechanisms of fish alloherpesviruses, due to the scarcity of knowledge relating to their envelope proteins. Our study showed that the nonionic surfactant TritonX-100 could effectively separate viral envelope in line with other previous reports [ 17 , 19 ], which may provide essential technical understanding for the identification and characterization of other putative envelope proteins.…”
supporting
confidence: 91%
“…However, little research has been performed concerning the molecular mechanisms of fish alloherpesviruses, due to the scarcity of knowledge relating to their envelope proteins. Our study showed that the nonionic surfactant TritonX-100 could effectively separate viral envelope in line with other previous reports [ 17 , 19 ], which may provide essential technical understanding for the identification and characterization of other putative envelope proteins.…”
supporting
confidence: 91%
“…Similar to the lytic replication cycle of herpesvirus (Sharma-Walia et al, 2005 ; Pan et al, 2006 ; Stahl et al, 2012 ), JNK1 and/or c-Jun phosphorylation enhanced SGIV immediate-early gene ORF086R and early gene ORF136 expressions. However, inhibition of phosphorylation of JNK and c-Jun by JNK1 mutant did not globally block the expression of viral genes contribute to the formation of virus factories and assembly, including the iridovirus ORF086R (Xia et al, 2009 ), structure protein ORF072 (Ou-yang et al, 2012b ) and ORF39L (Zhang et al, 2015 ). These data demonstrate that JNK1 is also essential to the late stage in the replication process of iridoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Equal amounts of cell lysate extracts were subjected to the SDS-PAGE and western blot analyses. The viral structure proteins of late stage gene ORF39L and ORF072 were detected using mouse anti-SGIV ORF39L serum (Zhang et al, 2015 ) and anti-SGIV ORF 072 serum (Ou-yang et al, 2012b ) at a dilution of 1:2000, respectively. The internal controls were β-actin that examined as method above.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, the viral titer is determined with TCID 50 , plaque formation unit or number of virions, and it has been frequently used in virus research 5 8 12 14 24 27 28 29 30 31 32 . The viral titer is measured depending on three major aspects, namely pathogenicity, infectivity and the number of infectious virions.…”
Section: Discussionmentioning
confidence: 99%
“…In the VAS, the protein encoded by orf019 and orf038 are finally assembled as envelope protein and capsid proteins respectively 12 13 . Most recently, late gene orf039 has been reported to encode envelope protein as a target in SGIV neutralization 14 , and orf075 has been found to encode a scaffold protein essential for virion packaging and structural stability 15 . However, key players and their precise roles in SGIV infectivity and pathogenicity have remained to be identified.…”
mentioning
confidence: 99%